Un soffitto viola - Nicola, Spinosi (Firenze University Press, 2005)
The book is offered as a reflection on psychological practice which, with a light touch of self-irony and a easy, flowing language, addresses various significant nodal aspects of the profession. The different chapters, approached in an autobiographical, diarial and critical key, focus analysis of various significant aspects of both the analytic practice and the training of the analyst. Considerable space is devoted, on the one hand to the narration and commentary of the dreams of the author and of his patients, and on the other to the role of politics in the training of those who, like the writer, began working as psychologists in the seventies. Thus the book is aimed both at professionals and students of psychology, and at a broader public which may be curious about who exactly is the person "on the other side of the couch".